2016
DOI: 10.1016/j.taap.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of arsenic-induced acquired cancer phenotype in prostate cancer stem cells by miR-143 restoration

Abstract: Inorganic arsenic, an environmental contaminant and a human carcinogen is associated with prostate cancer. Emerging evidence suggests cancer stem cells (CSCs) are the driving force of carcinogenesis. Chronic arsenic exposure malignantly transforms the human normal prostate stem/progenitor cell (SC) line, WPE-stem to arsenic-cancer SCs (As-CSCs), through unknown mechanisms. MicroRNAs (miRNAs) are small, non-coding RNAs that negatively regulate gene expression at the posttranscriptional level. In prior work, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The downregulation of miR-143 has been reported in ESCC, gastric cancer, colon cancer, prostate cancer, breast cancer, lung cancer, and several other cancers (20)(21)(22)(23)(24). Besides the critical roles in tumorigenesis, miRNAs have emerged as crucial regulators of T cell differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of miR-143 has been reported in ESCC, gastric cancer, colon cancer, prostate cancer, breast cancer, lung cancer, and several other cancers (20)(21)(22)(23)(24). Besides the critical roles in tumorigenesis, miRNAs have emerged as crucial regulators of T cell differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of miR-143 expression has also been reported in several human cancers, including colorectal cancer 23 , prostate cancer 26 , cervical cancer 27 , ovarian cancer 28 and B-cell lymphoma 29 . Thus, it is considered that miR-143 is a tumor-suppressor miRNA.…”
Section: Discussionmentioning
confidence: 82%
“…One recent study has shown that miR-143 was significantly down-regulated in Cr(VI)-transformed human bronchial epithelial BEAS-2B cells (He et al, 2013). As discussed above, the expression level of miR-143 was also found to be significantly decreased in arsenic-transformed human prostate stem cells and miR-143 re-expression greatly reduced malignant phenotypes of arsenic-transformed cells (Ngalame et al, 2014, 2015). Similarly, re-expression of miR-143 in Cr(VI)-transformed BEAS-2B cells significantly reduced their malignant phenotypes as evidenced by decreased mouse xenograft tumor angiogenesis and tumor growth (He et al, 2013).…”
Section: The Role Of Mirnas In Metal Carcinogen-induced Cell Maligmentioning
confidence: 71%
“…The authors concluded that arsenic induces malignant cellular transformation of human prostate cells by dysregulating the cellular miRNA profiles, which leads to an increase in the activation of oncogenic pathways such as RAS. Indeed, a recent follow-up study from the same group showed that restoration of miR-143, one of the significantly down-regulated miRNAs in arsenic-transformed prostate stem cells (As-CSC), greatly reduced multiple malignant phenotypes in the As-CSCs (Ngalame et al, 2015). …”
Section: The Role Of Mirnas In Metal Carcinogen-induced Cell Maligmentioning
confidence: 99%